1992
DOI: 10.1007/bf02451788
|View full text |Cite
|
Sign up to set email alerts
|

Uracil in Oris of herpes simplex 1 alters its specific recognition by origin binding protein (OBP): does virus induced uracil-DNA glycosylase play a key role in viral reactivation and replication?

Abstract: We have recently demonstrated that mammalian uracil-DNA glycosylase activity is undetectable in adult neurons. On the basis of this finding we hypothesized that uracil, derived either from oxidative deamination of cytosine or misincorporation of dUMP in place of dTMP during DNA repair by the unique nuclear DNA polymerase present in adult neurons, DNA polymerase beta, might accumulate in neuronal DNA. Uracil residues could also arise in the herpes simplex 1 (HSV1) genome during latency in nerve cells. We theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 19 publications
3
37
0
Order By: Relevance
“…The absence of the 5-methyl group in uracil has the potential to alter DNA structure and dynamic features that might be important for recognition by transcription factors or other DNA binding proteins (23,25). For example, uracils localized in the origin of replication in HSV-1 were found to perturb the binding of the HSV-1 origin binding protein (27), and incorporated uracils in the cAMP response element (CRE) of rat stomatostatin gene led to a two-to fourfold decrease in binding of CRE binding proteins from HeLa extracts (26). Our observation of reduced GFP expression from the exogenously uracilated DNA in the HT29-Ugi cell line supports the proposal that the presence of uracil in DNA can lead to reduced gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the 5-methyl group in uracil has the potential to alter DNA structure and dynamic features that might be important for recognition by transcription factors or other DNA binding proteins (23,25). For example, uracils localized in the origin of replication in HSV-1 were found to perturb the binding of the HSV-1 origin binding protein (27), and incorporated uracils in the cAMP response element (CRE) of rat stomatostatin gene led to a two-to fourfold decrease in binding of CRE binding proteins from HeLa extracts (26). Our observation of reduced GFP expression from the exogenously uracilated DNA in the HT29-Ugi cell line supports the proposal that the presence of uracil in DNA can lead to reduced gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In both EBV and HSV, the binding of OBP to the origin of lytic replication is absolutely required for viral DNA replication. In HSV, it has been demonstrated that uracil replacing either cytosine (mimicking cytosine deamination) or thymine (mimicking dUTP misincorporation) on site I of OriS diminishes the interaction between OBP and OriS in a gel shift assay (20). Thus, experiments to determine the effects of the binding of Zta to the uracil-containing Zta responsive element are awaited.…”
Section: Discussionmentioning
confidence: 99%
“…To express His-BKRF3 protein, pET15a-BKRF3 was transformed into BL21(DE3), and the bacteria were induced in the exponential phase with 1 mM IPTG at 37°C for 2 h. The cell extracts were homogenized in lysis buffer (20 Antibodies. To generate BKRF3-specific polyclonal antibodies, 6-week-old BALB/c mice were immunized with 50 g His-BKRF3 protein in complete Freund's adjuvant subcutaneously, followed by three boosters with incomplete Freund's adjuvant at 2-week intervals.…”
Section: Constructs and Strainsmentioning
confidence: 99%
“…Hence, it has been shown that uracil substitutions in the viral origins of replication alters their recognition by the viral initiator protein (5). Moreover, whereas UL2 may be dispensable for viral replication in fibroblast (6), UL2 mutants exhibit reduced neurovirulence and a decreased frequency of reactivation from latency (7).…”
mentioning
confidence: 99%